PRICE DISCOUNT, BONUS PACK, AND HEDONIC VALUE TOWARDS ONLINE SHOP IMPULSE BUYING: A CASE STUDY ON PRIVATE COLLEGE STUDENTS IN SUNGAI PENUH CITY - Intan Sherlin; Indra Budaya; Edwin Bustami (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
We study online shop impulse buying behaviour of college students in some private universities at Sungai Penuh city and formulate problems as follows: (1) how could price discount affect their impulse buying behaviour? (2) How could bonus packs affect their impulse buying behaviour? (3) How could hedonic value affect their impulse buying behaviour? (4) How could price discount, bonus pack, and hedonic value altogether affect their impulse buying behavior? We spread questionners among 60 students of private universities in Sungai Penuh city and use descriptive quantitative techniques for data analysis. Results of the study shows that there is a significant influence of price discounts and bonus packs, partially, on impulse buying behaviour of these college students. While the hedonic value has a little to no significant effect on their impulse buying behaviour. For price discounts, bonus packs, and hedonic values altogether, there is a significant effect on impulse buying behaviour simultaneously. The influence of price discount, bonus pack, and hedonic value on impulse buying behaviour is 16.9%, with 83.1% are from another influences that need to be further studied for future research.